2016
DOI: 10.1016/j.jclinane.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The intraoperative glycemic response to intravenous insulin during noncardiac surgery: a subanalysis of the DeLiT randomized trial

Abstract: Summary Patient characteristics may affect patients' response to insulin. We examined the impact of body weight, and presence of diabetes on the response to insulin during non-cardiac surgery. We studied 202 patients who were enrolled in the DeLiT Trial and received intraoperative intravenous insulin. Univariable and multivariable analyses (Bonferroni-corrected) assessed the relationship between patient's response to the initial intraoperative bolus of regular insulin and the factors of interest. Blood glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…22 The abstract was excluded due to inability to obtain full data set from corresponding author. Twenty-five publications were excluded due to failure to meet inclusion criteria: eight were review articles, 23–31 seven were cohort studies rather than randomized controlled clinical trials, 3237 six evaluated outcome other than postoperative delirium or postoperative cognitive dysfunction, 34,3841 two were still ongoing at time of publication, 32,42 one used a different variable than processed electroencephalogram-guided care 43 and one used a data set from a trial already included. 34…”
Section: Resultsmentioning
confidence: 99%
“…22 The abstract was excluded due to inability to obtain full data set from corresponding author. Twenty-five publications were excluded due to failure to meet inclusion criteria: eight were review articles, 23–31 seven were cohort studies rather than randomized controlled clinical trials, 3237 six evaluated outcome other than postoperative delirium or postoperative cognitive dysfunction, 34,3841 two were still ongoing at time of publication, 32,42 one used a different variable than processed electroencephalogram-guided care 43 and one used a data set from a trial already included. 34…”
Section: Resultsmentioning
confidence: 99%
“…According to studies, patients with DM are more likely to undergo surgery, and DM is the most common endocrine disease anesthesiologist deals with ( 6 , 7 ). Several observational and interventional studies have shown that hyperglycemia is accompanied by increased mortality risk, morbidity after major surgery, especially cardiac surgery, dehydration, electrolyte impairment and delay in wound and infection healing, postoperative inflammation, hospital stay prolongation, cardiac complications, and acute renal failure (secondary to increased oxidative stress in xanthine path and urinary excretion of inflammatory cytokine among patients with and without DM) after surgery ( 8 - 12 ). Van den et al showed that accurate glycemic control in the range of 80-110 mg/dl was effective in reducing short-term mortality (30 days), sepsis reduction, surgery site infections, atrial fibrillation, and acute kidney injury after surgery, especially in cardiac surgery groups, albeit a higher chance of hypoglycemia (< 70 mg/dl) ( 13 ).…”
Section: Introductionmentioning
confidence: 99%